STUDENTS’ READING ABILITY OF NARRATIVE TEXTS : (A Study at SMAN 2 VII Koto Sungai Sariak of Padang Pariaman Regency - Septy, Adzanil Prima; Utami, Lara Diah (Indra institute Research & Publication, 2024)
This descriptive research aimed to assess the reading comprehension abilities of students regarding narrative texts at SMAN 2 VII Koto Sungai Sariak of Padang Pariaman regency. The study utilized stratified cluster random sampling to select a sample of 60 students and collected data through a reading test. The study revealed that the students' overall ability to read narrative texts was low. Specifically, 65% of the students struggled to comprehend narrative texts. Within the narrative text components, 51% of students had difficulty understanding the orientation, 63% had trouble with the complication, 55% struggled with the resolution, and 67% found the reorientation challenging. Despite these difficulties, the study highlighted issues with students' learning motivation and the effectiveness of teaching strategies within the context of the current curriculum implementation, Kurikulum Merdeka. Based on these findings, the study recommends that English teachers should review and possibly revise the narrative text lesson materials and teaching strategies to make them more engaging and motivational for students. This is crucial for the successful implementation of the Kurikulum Merdeka, with the teacher profile of Guru Penggerak being a key factor in developing students' character and reading skills in English. Additionally, the study suggests focusing on vocabulary development to facilitate better comprehension of English texts. Future research should investigate the underlying causes of students' difficulties with reading narrative texts to develop more effective interventions.